2021
DOI: 10.1088/1755-1315/915/1/012023
|View full text |Cite
|
Sign up to set email alerts
|

The impact of e-commerce on the sustainable development: case of Ukraine, Poland, and Austria

Abstract: The COVID-19 pandemic dramatically and irreversibly transformed global e-commerce trends. The process of internationalization has been slowed down considerably, the level of globalization impact has decreased, that, consequently, has led to a strong lag in the development of some countries. The aim of the study is to determine the nature of e-commerce socio and economic effects in Ukraine, Poland, and Austria. For analysis, a modern mathematical apparatus was used – the Cobb-Douglas model and the Markov chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Through the research on e-commerce development in Ukraine, Poland, et al (2021) found that the stability of e-commerce investment can help countries recover their economic vitality from the COVID-19 epidemic faster and create more employment opportunities and business development opportunities [9]. Merzlyakova (2021) found that the global growth rate of e-commerce is very high, and its good prospects attract more and more participants [10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Through the research on e-commerce development in Ukraine, Poland, et al (2021) found that the stability of e-commerce investment can help countries recover their economic vitality from the COVID-19 epidemic faster and create more employment opportunities and business development opportunities [9]. Merzlyakova (2021) found that the global growth rate of e-commerce is very high, and its good prospects attract more and more participants [10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…O. Fedirko et al (2021) analysed the nature of socio-economic effects of e-commerce in Ukraine, Poland, and Austria using the Cobb-Douglas mathematical model and Markov chain methodology. The study showed a significant positive impact of e-commerce on employment and gross domestic product in three countries.…”
Section: Introductionmentioning
confidence: 99%
“…Cryptocurrencies are already widely used in electronic payment systems (for example, stocks from Burger King and Coca Cola with unique gifts for those who used cryptocurrency for payments). The world's largest companies that use cryptocurrency payments in e-commerce rely on market leaders of cryptocurrency payment providers such as BitPay, Coinbase, Flexa, or create their own integrations with cryptocurrency networks [9,10].…”
Section: Introductionmentioning
confidence: 99%